2020
DOI: 10.1080/09243453.2020.1812675
|View full text |Cite
|
Sign up to set email alerts
|

Promoting primary school pupils’ language achievement: investigating the impact of school-based language policies

Abstract: School-based language policies (SLP) are expected to have a positive effect on student achievement. To date, few studies have empirically examined the impact of such policies on student outcomes. This study investigates to what extent SLPs are related to pupils' reading performance from an educational effectiveness perspective. In addition, the study investigates whether SLPs have differential effects for pupils at risk of underachievement. Data from a cross-sectional study involving 3,000 pupils in the first,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Many studies into the role of the school context in policy execution in the classroom have so far taken the form of qualitative and quantitative case studies. These studies revealed the impact of language policy in education as well as the results of language policy implementation in education 4 . The findings indicate that one SLP element, team indicative capacity for language lessons, improves students' reading word recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies into the role of the school context in policy execution in the classroom have so far taken the form of qualitative and quantitative case studies. These studies revealed the impact of language policy in education as well as the results of language policy implementation in education 4 . The findings indicate that one SLP element, team indicative capacity for language lessons, improves students' reading word recognition.…”
Section: Introductionmentioning
confidence: 99%